Factor reumatoide: asociación con la erosión radiológica y actividad de la artritis reumatoide Rheumatoid factor: association with the radiological erosion and with the rheumatoid arthritis activity - Elena Kokuina (Revista Cubana de Medicina, 2008)
OBJETIVO: Definir la relación del factor reumatoide (FR) con la erosión articular radiológica, la actividad de la enfermedad y la discapacidad funcional de la artritis reumatoide (AR). MÉTODOS: Se realizó un estudio transversal con 209 pacientes con AR establecida, de estos, 74 con AR de corta evolución (= 2 años). Se evaluaron los indicadores siguientes: FR por aglutinación del látex (FR-A), FR por inmunoturbidimetría automatizada (FR-T), velocidad de eritrosedimentación (VSG), proteína C reactiva (PCR), índice de actividad de la enfermedad (Disease Activity Score 28, DAS28), índice de discapacidad funcional (Health Assessment Questionnaire score, HAQ) y la presencia de erosiones radiológicas. RESULTADOS: El 77 % de los pacientes positivos de FR-A y el 73 % de los positivos para el FR-T presentaron erosiones radiológicas, opuestamente al 38 % de los negativos para el FR-A (p<0,001) y al 14 % de los negativos para el FR-T (p<0,001). Las cifras medias del FR-A de los pacientes según los 4 grados de afectación articular (máximo: > 6 articulaciones erosionadas; mínimo: 0 erosión, < 6 articulaciones inflamadas) fueron de: 484; 162; 57 y 17 UI/mL (p<0,001); y las del FR-T de: 277; 185; 22 y 33 UI/mL (p<0,01). El valor predictivo positivo (VPP) para la erosión del FR-A >512 UI/mL fue de 92 % y el del FR-T >97 UI/mL fue de 96 %. Los valores medios del DAS28 en los pacientes positivos de FR-A y FR-T fueron de 5,04 y 4,94, respectivamente, mientras que, en los negativos fueron de 4,26 y 3,97 (p<0,001 para ambos); y los del HAQ de 1,31 y 1,29 en los positivos de FR-A y FR-T, respectivamente, mientras que en los negativos de 0,99 y 0,89 (p<0,01 para ambos). Se encontró correlación entre las cifras del FR por ambos métodos y las de VSG, PCR, DAS28 y HAQ (p<0,05 o p<0,01). CONCLUSIONES: Niveles altos del FR se corresponden con un grado mayor de inflamación y destrucción articular en la AR. OBJECTIVE: to define the relation of the rheumatoid factor with the radiological articular erosion, the activity of the disease and the functional disability of rheumatoid artritis (RA). MÉTHODS: A cross-sectional study was conducted among 209 patients with RA. Of them, 74 with RA of short evolution (= 2 years). The following indicators were evaluated: RhF by latex agglutination (RhF-A), RhF by automated immunoturbidimetry (RhF-T), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), Disease Activity Score 28 (DAS 28), functional disability index (Health Assessment Questionnaire score, HAQ), and the presence of radiological erosions. RESULTS: 77 % of the RhF-A positive patients and 73 % of the RhF-T positive patients presented radiological erosions in contrast with 38 % of the RhF-A negative patients (p<0.001) and with 14 % of the RhF-T negative cases (p<0.001). The mean RhF-A figures of the patients according to the 4 grades of articular affectation (maximum: > 6 eroded articulations; minimum: 0 erosion; < 6 swollen articulations) were 484, 162, 57 and 17 UI/mL (p<0.001), whereas those of RhF-T were 277, 185, 22 and 33 UI/mL (p<0,01). The positive predictive value (PPV) for the erosion of RhF-A >512 UI/mL was 92 %, and that of RhF-T >97 UI/mL was 96 %. The mean values of DAS28 in the RhF-A and RhF-T positive patients were 5.04 and 4.94, respectively. In the negative, these values were 4.26 and 3.97 (p<0.001 for both). The HAQ values were 1.31 and 1.29 in the RhF-A and RhF-T positive patients, respectively, while in the negative they were 0.99 and 0.89 (p<0.01 for both). Correlation was found between the RhF figures by both methods and those of ESR, CRP, DAS28 and HAQ (p<0.05 or p<0.01). CONCLUSIONS: High levels of RhF correspond with a higher degree of inflammation and articular destruction in the rheumatoid arthritis.